Model Pengelolaan Sumber Daya Kelautan dan Kemaritiman - Tjiptabudy, Jantje; Angga, La Ode; Latupono, Barzah (PAMALI: Pattimura Magister Law Review, 2024)
Introduction: Indigenous people who live on small islands are quite large in number compared to the available natural resources. So it can be said that it is not enough to meet the basic needs of indigenous peoples, for a certain period of time. Therefore, the idea was born to create legal regulations that could regulate and organize all the potential of marine and maritime resources so that they could be used wisely.Purposes of the Research:  to formulate the formulation of a Marine and Maritime Resources Management Model in Central Maluku Regency.Methods of the Research: This research was conducted using an empirical juridical approach which is a descriptive qualitative analysis study.  The research seeks to describe the Marine and Maritime Resource Management Model in Central Maluku Regency. The way the empirical juridical or sociological juridical method works in this research proposal is from the results of collecting and finding data and information through literature study of the basic assumptions or presumptions used in answering the problems in this research, then inductive-verification testing is carried out on the latest facts available. exists in society, thus the truth in a study has been declared reliable without having to go through a rationalization process.Results of the Research: To minimize conflicts and disputes that occur in the marine and maritime customary rights community, there must be a formulation of a model for regulating marine and maritime management in Central Maluku Regency involving all cuttings holders.